O processo de distritalização e a utilização de serviços de saúde - avaliação do caso de Pau da Lima, Salvador, Bahia, Brasil District allocation and utilization of health care services in Pau da Lima, Salvador, Bahia, Brazil - Lígia Maria V. da Silva; Vera Lúcia A. Formigli; Macius P. Cerqueira; Leonardo Kruchevsky; Márcia Maria A. Teixeira; Antonio Sergio M. Barbosa; Paulo Sergio de A. Conceição; Mauro de A. Khouri; Carlito L. Nascimento (Escola Nacional de Saúde Pública, Fundação Oswaldo Cruz, 1995)
Foi realizado estudo transversal de utilização de serviços de saúde no Distrito Sanitário de Pau da Lima, Salvador, Bahia, Brasil, em 1992, a partir de inquérito domiciliar com recurso à técnica de amostragem por conglomerados. Entre as 1887 pessoas moradoras dos 384 domicílios visitados, 236 haviam utilizado serviços de saúde nos últimos 30 dias, correspondendo à taxa global de utilização de 12,5%. Os serviços públicos do distrito foram responsáveis por 25,9% do total dos atendimentos, tendo ocorrido maior utilização na faixa etária entre 15 e 29 anos (29,8%) e no sexo feminino (73,7%). A escolha do tipo de serviços foi influenciada principalmente por razões relacionadas com a acessibilidade (63,7%). A procura dos serviços decorreu sobretudo de motivos relacionados com a ocorrência de doença e com a busca de serviços curativos (75,7%). Esses achados revelam incipiência no processo de distritalização, expresso tanto em insuficiências quantitativas relacionadas com a cobertura assistencial e a oferta de serviços, quanto em problemas organizacionais que fazem com que a produção ainda não utilize preferencialmente os serviços do Distrito. Os autores discutem esses resultados no atual contexto de expansão do setor privado e de colapso de financiamento setorial. This cross-sectional study is aimed at the identication of patterns in the utilization of health care services in Pau da Lima, a neighborhood in the city of Salvador, Bahia. In 1992, a household survey was carried out with 384 families selected through a random cluster sampling design. In each household, the family head or a surrogate informant was asked to answer a questionnaire about their use of any type of health care in the last month. From the total of 1,887 individuals, 236 reported at least one visit to health facilities during the referent period This means an estimated prevalence of health services utilization of 12.5%. With regard to the type of services, 25.9% of all visits were made to public sector facilities. Attendants were mainly women (73.7%) from 15 to 29 years of age. The main reason reported for the choice of the health facility was availability (63.7%), and the major reason for seeking health care was disease-related conditions (75.7%), rather than preventive procedures. These findings may result from the still unfinished process of distritalização(district allocation of services), which is evident in the lack of health services' infrastructure or coverage, as well as in persistent organizational problems. These issues may lead the population living in the respective district to seek health care outside the assigned catchment area. The authors discuss these findings in the context of the expansion of the private sector in the health area and the financial collapse of the public budget in Brazil.